Assessment of Community-led Total Sanitation Sustainability in Ejigbo Local Government Area of Osun State, Nigeria - H. O. Sawyerr; A. A. Adepoju (Archives of Current Research International, 2019)
Nigeria is among the nations of the world with the highest number of people practising Open Defecation. This study among others assessed the level of community-led total sanitation (CLTS) in the selected triggered communities and focused on the rationale for the reversion of CLTS programme implemented in some of some rural communities with poor sanitation coverage in Ejigbo Local Government Area of Osun state, Nigeria, with the technical and financial support of donor agencies. The qualitative, semi-structured questionnaires were administered in 296 households in 41 selected communities. Spatial positioning of communities and water points coordinates were collected through the use of a hand-held Global Positioning System- GPS model etrex 10 GARMIN to produce a digital map through the Arc view Geographical Information System software. Two batches of CLTS were conducted in the Local Government Area across 182 communities in 2006 and 2012 with and without subsidy. Communities were triggered and declared open defecation free while some were certified ODF. The majority (75.7%) of the respondents reverted to OD as a result of caved-in of pit latrine due to the use of log of wood, wooden slab as platform over the pit. 5.1% of the respondents improved on CLTS latrine 81.7% of household used the latrine for just two years before defectiveness set in. All respondents agreed to have benefited in the CLTS programme and were willing to return to construct durable latrine provided they get a subsidy or are financially buoyancy. This study revealed that emphasis was on latrine construction while other components of environmental sanitation were not properly addressed as any scalability was near to nothing. Monitoring and follow up was found to be weak among the stakeholders.